Uzbekistan – Bridge country on a CO2-neutral path - Kress, Hannelore [Verfasser] (My University, 2024)
„Uzbekistan experienced impressive economic growth for years. This led to environmental problems such as soil salinisation, high methane emissions and air pollution. Since the change of power in 2016, the country opened up to foreign investment and has since been striving for a „green economy“. With the ratification of the Paris Agreement in 2018, ambitious targets are implemented to reduce greenhouse gas emissions and decrease pollution. To realize the transformation to a green economy, Uzbekistan is investing massively in education and skilled workforce training.“ (author‘s abstract; BIBB-Doku)
Keywords: G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; I 2.3.4 Asien; 370; 330; Wirtschaftsentwicklung; Umweltpolitik; Berufsausbildung; Green skills / Grüne Kompetenzen; Usbekistan